2020
DOI: 10.1016/j.cryobiol.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The harmful effect of removing the extracellular vitrification medium during embryo cryopreservation using a nylon mesh device in rabbit

Abstract: During the last decades, many techniques have been developed to reduce sample volume and improve cooling and warming rates during embryo vitrification. The vast majority are based on the "minimum drop size" concept, in which the vitrification solution around embryos is reduced by aspiration, leaving a tiny part of volume surrounding embryos.However, novel cryodevices were aimed to remove the entire vitrification solution. This study was designed to compare the "minimum drop size" technique using Cryotop® with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In addition, cryopreservation is known for its harmful impacts on embryonic health, placing embryos at risk from a variety of types of cryoinjury during temperature and phase transitions [ 18 , 27 ]. Such survival impairment is in agreement with previous studies performed in rabbits, where manipulations of either fresh or vitrified embryos resulted in negative developmental effects both under in vitro conditions and in vivo [ 22 , 23 , 26 , 28 , 29 , 30 ]. It has been reported that successful hatching is dependent on a sufficiently high number of embryonic cells, which enables blastocyst expansion and zona shedding [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, cryopreservation is known for its harmful impacts on embryonic health, placing embryos at risk from a variety of types of cryoinjury during temperature and phase transitions [ 18 , 27 ]. Such survival impairment is in agreement with previous studies performed in rabbits, where manipulations of either fresh or vitrified embryos resulted in negative developmental effects both under in vitro conditions and in vivo [ 22 , 23 , 26 , 28 , 29 , 30 ]. It has been reported that successful hatching is dependent on a sufficiently high number of embryonic cells, which enables blastocyst expansion and zona shedding [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In oocyte vitrification, a decrease in cryosurvival rate due to the use of closed devices has been reported [31]. However, Cryotop and mini-straws had a similar embryonic development in rabbit species [24], but slightly less than the in vitro development, compared with fresh embryos [24,32,33]. Bielanski et al [13] showed that Cryotop-closed with a straw cap system and straws had the same embryo development results after a year of storage, with a lower potential danger of embryo contamination.…”
Section: Discussionmentioning
confidence: 99%